Mathematics Learning With The Flipped-Mastery Model: Improving Students’ Creative Thinking in Senior High School - Ratu Mauladaniyati, Wahyudin, Endang Cahya Mulyaning (International Journal of Control and Automation, 2020)
This study aims to obtain a picture of improving students' creative thinking skills in mathematics learning with the Flipped-Mastery model. This study is an experimental study with a nonequivalent pre-test post-test control group design. With a population of all students of SMA N 1 Pandeglang, and the sample is students of MIPA X-4 class as an experimental class and MIPA X-5 class as a control class. The instrument used was a creativity test instrument consisting of 4 essay questions. Data analysis uses gain data which is in conflict with the two mean difference test, the t test to determine better creative thinking abilities for improvement. The results showed that increasing the creative thinking ability of students who learned the Flipping-Mastery model were better than students who obtained conventional learning. This research can contribute in learning mathematics because it is one of the learning models according to the guidelines of the current era.